A Critical Review of Current Crisis Simulation Methodology - Kim, Hak-Kyong; Lee, Ju-Lak (International JOURNAL OF CONTENTS, 2011)
This paper is concerned with simulation exercises used to train key response agencies for crisis situations. While ‘multi-agency’ simulations are increasingly acknowledged as a necessary and significant training tool for emergency response organisations, many current crisis simulations are still focused on the revision of existing response plans only. However, a crisis requires a rapid reaction, yet in contrast to an ‘emergency’, the risks for critical decision makers in crisis situations are difficult to measure, owing to their ill-structure. In other words, a crisis situation is likely to create great uncertainty, unfamiliarity and complexity, and consequently should be managed by adaptive or second order expertise and techniques, rather than routine or structured responses. In this context, the paper attempts to prove that the current practices of simulation exercises might not be good enough for uncertain, unfamiliar, and complex ‘crisis’ situations, in particular, by conducting case studies of two different underground fire crises in Korea (Daegu Subway Fire 2003) and the UK (King’s Cross Fire 1987). Finally, it is suggested that the three abilities: ‘flexibility’, ‘improvisation’ and ‘creativity’ are critical in responding to a crisis situation. This paper is concerned with simulation exercises used to train key response agencies for crisis situations. While ‘multi-agency’ simulations are increasingly acknowledged as a necessary and significant training tool for emergency response organisations, many current crisis simulations are still focused on the revision of existing response plans only. However, a crisis requires a rapid reaction, yet in contrast to an ‘emergency’, the risks for critical decision makers in crisis situations are difficult to measure, owing to their ill-structure. In other words, a crisis situation is likely to create great uncertainty, unfamiliarity and complexity, and consequently should be managed by adaptive or second order expertise and techniques, rather than routine or structured responses. In this context, the paper attempts to prove that the current practices of simulation exercises might not be good enough for uncertain, unfamiliar, and complex ‘crisis’ situations, in particular, by conducting case studies of two different underground fire crises in Korea (Daegu Subway Fire 2003) and the UK (King’s Cross Fire 1987). Finally, it is suggested that the three abilities: ‘flexibility’, ‘improvisation’ and ‘creativity’ are critical in responding to a crisis situation. KCI Citation Count: 1